Serum myostatin levels are associated with abdominal aortic calcification in dialysis patients - Su Mi Lee; Seong Eun Kim; Ji Young Lee; Hyo Jin Jeong; Young Ki Son; Won Suk An (The Korean Society of Nephrology, 2019)
Background : Serum myostatin levels are increased according to renal function decline and myostatin may be a main mediator of chronic kidney disease-related sarcopenia. A previous study reported that serum myostatin level was negatively associated with abdominal aortic calcification (AAC) in older males. The aim of this study was to assess the association between serum myostatin level and AAC among dialysis patients of both sexes. In addition, we analyzed the relationship between serum myostatin level, muscle mass, and bone mineral density (BMD).Methods : In this cross-sectional study, we evaluated AAC in the lateral lumbar spine using plain radiography and BMD in 71 patients undergoing dialysis. We classified patients into two groups according to the median value of myostatin as follows: those with high myostatin levels (≥ 5.0 ng/mL) and those with low myostatin levels (< 5.0 ng/mL).Results : The proportion of patients with an AAC score of five points or more was higher among those with low myostatin levels. Myostatin level was negatively associated with AAC scores on plain radiography and had a positive association with skeletal muscle mass and T-scores for BMD measured at the total hip and femur neck. Lower myostatin levels were independently associated with higher AAC scores following adjustment for age, sex, diabetes mellitus, dialysis vintage, dialysis modality, and osteoprotegerin level.Conclusion : Lower serum myostatin levels were associated with higher AAC scores, lower muscle mass, and lower BMD in dialysis patients. Further, prospective studies and those with larger cohorts are necessary to validate these findings.